2014
DOI: 10.1097/iae.0b013e3182993f11
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Domain Optical Coherence Tomography Findings in Patients With Acute Syphilitic Posterior Placoid Chorioretinopathy

Abstract: Patients with acute syphilitic posterior placoid chorioretinitis show characteristic outer retinal abnormalities on SD OCT imaging, including disruption of the inner segment/outer segment band, nodular thickening of the RPE with loss of the linear outer segment/RPE junction, and, in some cases, loss of the external limiting membrane, accumulation of subretinal fluid, and punctate hyperreflectivity in the choroid. Vision improved and these abnormalities reversed after treatment of neurosyphilis in most of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
125
2
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(147 citation statements)
references
References 29 publications
11
125
2
9
Order By: Relevance
“…Despite their findings Eandi et al disclosed an overall prevalence of subretinal fluid in 11 of 93 eyes (11.8 %) reported in the literature. Furthermore, a recent study Pichi et al [182] focused on 30 eyes of 19 confirmed cases with acute syphilitic posterior placoid chorioretinopathy from 12 separate international centers. SD OCT was performed at different stages of the disease and showed uniform presence of a small amount of fluid under the fovea at 1-2 days after presentation in 13 of the 30 eyes.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Despite their findings Eandi et al disclosed an overall prevalence of subretinal fluid in 11 of 93 eyes (11.8 %) reported in the literature. Furthermore, a recent study Pichi et al [182] focused on 30 eyes of 19 confirmed cases with acute syphilitic posterior placoid chorioretinopathy from 12 separate international centers. SD OCT was performed at different stages of the disease and showed uniform presence of a small amount of fluid under the fovea at 1-2 days after presentation in 13 of the 30 eyes.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Since spirochetes are effectively eradicated by the engulfing activity of macrophages, we can deduce that phagocytosis of the RPE is also effective in eliminating this microorganism. SD-OCT imaging of ASPPC reveals irregular hyperreflectivity of the RPE with prominent nodular elevation [3]. This also suggests the possibility that RPE layers are crucially involved in the mechanism of ASPPC.…”
Section: Discussionmentioning
confidence: 81%
“…SD-OCT imaging can reveal prominent nodular elevation of the RPE that can persist for up to 1 month after treatment [3].…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the inner/outer photoreceptor segment (IS/OS) junction, thickening and granular hyperreflectivity of the RPE and loss of choroidal vascular detail are common OCT findings. 9,10 The ophthalmoscopic, angiographic, and OCT findings in ASPPC seem to suggest a pathophysiologic process of active inflammatory reaction at the level of the choriocapillaris-RPE-retinal photoreceptor complex.…”
mentioning
confidence: 99%